Total quality management in industrialised building system: Implementation and benefits in construction projects - Mohsen Alawag, A. (Ain Shams University, 2022)
Total quality management (TQM) is widely regarded as one of the most important approaches toward improving the quality of an organization's output in the construction industry. The industrialized building system (IBS) or prefabrication process has been described as a valid alternative for replacing traditional construction methods in terms of quality, cost-effectiveness, protection and health, waste mitigation, and productivity. This study aims to identify and rank the critical success factors that affect TQM in Malaysian IBS construction projects. The collected questionnaire data was subjected to statistical analysis. The analysis showed that the most important grouped factor is leadership. Regardless of the identified critical factor, all contributing factors established a significant influence on the successful performance. The study developed a conceptual framework based on the top critical factors that will help stakeholders to enter before applying TQM in IBS construction projects. Â© 2022 THE AUTHORS